Resistive switching in a GaOx-NiOx p-n heterojunction - Sun, Xiaowei (2013)
We report a unidirectional bipolar resistive switching in an n-type GaOx/p-type NiOx heterojunction fabricated by magnetron sputtering at room temperature. The resistive switching behavior coincides with the switching between Ohmic conduction (low resistance) and rectifying behavior (high resistance) of the heterojunction diode. Under external electric field, electromigrated intrinsic defects, such as oxygen vacancies and oxygen ions, accumulate at the pn junction interface and modify the interface barrier, forming or rupturing the filamentary paths between n-GaOx and p-NiOx, leading to the switching between Ohmic and diode characteristics of the device. The device shows good endurance, retention performance, and scaling capability, signaling the potential of a diode-structured resistive switching device for non-volatile memory applications.